2005
DOI: 10.1097/01.icu.0000179802.04101.79
|View full text |Cite
|
Sign up to set email alerts
|

Mucous membrane pemphigoid: an update

Abstract: Further advances have been achieved in the field of mucous membrane pemphigoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 22 publications
0
14
1
2
Order By: Relevance
“…The differential diagnosis for cicatrising conjunctivitis is broad and includes OCP, Stevens Johnsons syndrome, chemical burns, radiation, toxic conjunctivitis, post-infectious conjunctivitis, graft versus host disease, atopic keratoconjunctivitis and conjunctival squamous cell carcinoma 1. Paraneoplastic pemphigoid should also be considered in the differential diagnosis, and this case illustrates the importance of obtaining a pertinent history and review of systems.…”
Section: Commentmentioning
confidence: 95%
See 2 more Smart Citations
“…The differential diagnosis for cicatrising conjunctivitis is broad and includes OCP, Stevens Johnsons syndrome, chemical burns, radiation, toxic conjunctivitis, post-infectious conjunctivitis, graft versus host disease, atopic keratoconjunctivitis and conjunctival squamous cell carcinoma 1. Paraneoplastic pemphigoid should also be considered in the differential diagnosis, and this case illustrates the importance of obtaining a pertinent history and review of systems.…”
Section: Commentmentioning
confidence: 95%
“…It is characterised by linear deposition of immunoglobulins and complement along epithelial basement membranes 1. In this report, we describe a cicatrising conjunctivitis that was clinically and pathologically similar to ocular cicatricial pemphigoid but occurred concurrently with systemic malignancy.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…10,11 Additionally, the complex interplay between the immune system and conjunctival cells contributes to production of proinflammatory cytokines, chemokines, and chemical factors. [12][13][14] Studies on the natural history of this entity have shown a marked degree of clinical and immunologic variability, ranging between mild cases that progress slowly and more severe clinical forms with a progressing-relapsing course even under treatment. 15,16 The chronic, and sometimes unpredictable course of the disease makes it difficult to determine whether the favorable effects of short-term treatment will be sustained.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly affected area is the oral cavity (90%), with the eyes (65%), nose, nasopharynx, anogenitals, skin (20%-30%), larynx, and esophagus involved less often. 3 Oral disease is characterized by erythematous patches, blisters, erosions, and ulcerations. 4 The primary feature of ocular MMP is progressive, conjunctival fibrosis.…”
Section: Solutionmentioning
confidence: 99%